Listening-based Communicative Instructional Approach at the Indonesian Gigantic Immersive Environment - Widya Rizky Pratiwi (Pascasarjana UM, 2022)
Abstract: Creative Innovation in teaching critically influences students' success. This paper investigates teachers' teaching methods in an Indonesian gigantic English immersive Environment. The qualitative study, which involved eight participants, was conducted in a